New trends in databases and information systems : ADBIS 2016 Short Papers and Workshops, BigDap, DCSA, DC, Prague, Czech Republic, August 28-31, 2016, Proceedings /: ADBIS 2016 Short Papers and Workshops, BigDap, DCSA, DC, Prague, Czech Republic, August 28-31, 2016, Proceedings. (2016) - Unknown
No abstract available